A three-component, one-pot synthesis of 1,8-naphthyridine and isoxazole derivatives and computational elucidation of the mechanism - ERDEM, SAFİYE (SPRINGER, 2019)
An efficient and general method for the synthesis of substituted 3,4-dimethylisoxazolo[5,4-b]pyridine-5-carboxamide and benzo[b][1,8]naphthyridine-3-carboxamide derivatives by using 2,2,6-trimethyl-4H-1,3-dioxin-4-one, benzyl amine, aromatic aldehydes, 2-aminoquinoline, or 5-amino-3-methylisoxazole in the presence of a catalytic amount of p-toluenesulfonic acid or iodine is described. The formation of the products was investigated and the results obtained were also supported by theoretical calculations.
Keywords: Isoxazoles; 1,8-Naphthyridines; Catalyst; Conjugated heterocycles; Computational studies; PATH; AROMATICITY; CONTINUUM; OXIDATION; KINETICS; ANALOGS